PARTISIPASI POLITIK PENYANDANG DISABILITAS DALAM PEMILIHAN KEPALA DAERAH KOTA PEKANBARU TAHUN 2017 DI KECAMATAN TENAYAN RAYA - Afriliya Sabatini; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine how big the involvement of people with disability in the form of decisions, and what are the obstacles to disability in the election process of Mayor and Vice Mayor of Pekanbaru 2017 in Tenayan Raya District. The form of political participation from persons with disbailitas is like. Participate in campaigns, and join in community organizations. The method used in this research is using descriptive quantitative approach. Against a total of 20 respondents with disabilities in Tenayan Raya District determined through accidental sampling. Data analysis was performed using cross tabulation analysis through SPSS program. Based on the results of the study indicates that political participation by persons with disabilities, in the election of Mayor and Vice Mayor of Pekanbaru in Tenayan Raya Sub-district, has not shown full and effective participation based on equality with other citizens. Where 50% of respondents who participate in politics, is joining in community organizations. However, in the participation of voting rights in the TPS, and following the campaign activities in the electoral process, the participation of respondents is still low. Some findings also indicate the obstacles of the Mayor and Mayor of Pekanbaru 2017 are in the form of administration, accessibility and assistance. Keywords: Political Participation Rate, Disability, Pilkada